2013
DOI: 10.1016/j.crohns.2012.04.008
|View full text |Cite
|
Sign up to set email alerts
|

Proinflammatory cytokines induce crosstalk between colonic epithelial cells and subepithelial myofibroblasts: Implication in intestinal fibrosis

Abstract: Our study indicates that colonic epithelial cells may respond to an inflammatory milieu by inducing myofibroblast functions similar to those observed during intestinal fibrosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
54
1
7

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 76 publications
(64 citation statements)
references
References 38 publications
2
54
1
7
Order By: Relevance
“…We examined in vitro the effect of phospholipids on the collagen production and proliferation/migration of myofibroblasts. We have previously demonstrated that TGFb1 can increase both collagen production and myofibroblast migration [22,41]. In this study, treatment of myofibroblasts with various concentrations of phospholipids resulted in a statistical significant reduction of both basal and TGFb1-induced collagen production.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…We examined in vitro the effect of phospholipids on the collagen production and proliferation/migration of myofibroblasts. We have previously demonstrated that TGFb1 can increase both collagen production and myofibroblast migration [22,41]. In this study, treatment of myofibroblasts with various concentrations of phospholipids resulted in a statistical significant reduction of both basal and TGFb1-induced collagen production.…”
Section: Discussionmentioning
confidence: 80%
“…Myofibroblast migration was assessed in vitro with the wound healing scratch assay that resembles wound healing and is dependent on myofibroblast migration, as previously described [21,22]. Forty-eight hours before the assay, the FBS concentration in the media was gradually reduced from 10%e 5% to minimize the contribution of proliferation.…”
Section: Wound Healing Scratch Assaymentioning
confidence: 99%
“…Recently, we have shown that stimulation of human SEMFs with proinflammatory cytokines results in production of tumor necrosis factor (TNF)-like ligand 1A (TL1A), a molecule recently implicated in both T-cell differentiation and intestinal fibrosis [33]. Concerning their possible participation in post-inflammatory intestinal fibrosis, SEMFs have been found to respond to proinflammatory and profibrotic cytokines, such as IL-17A [34] and TGF-β [35], by increasing production of collagen and MMPs. Finally, we have shown that conditioned medium from epithelial cell cultures stimulated with proinflammatory cytokines can enhance SEMF migration, and production of collagen and MMPs, suggesting the existence of a crosstalk between SEMFs and overlying epithelial cells during intestinal inflammation that can generate profibrotic responses [35].…”
Section: The Activated Myofibroblastmentioning
confidence: 99%
“…This has important implications on the crosstalk between subepithelial myofibroblasts and epithelial cells that regulate each other’s function. Epithelial cells respond to the paracrine stimuli from myofibroblasts to increase their TGF-β1 and TIMP-1 expression 42 .…”
Section: Cellular Basis Of Fibrosismentioning
confidence: 99%